2012
DOI: 10.1269/jrr.11140
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53-Regulated Proteins in Human Cultured Lymphoblastoid TSCE5 and WTK1 Cell Lines during Spaceflight

Abstract: The aim of this study was to determine the biological effects of space radiations, microgravity, and the interaction of them on the expression of p53-regulated proteins. Space experiments were performed with two human cultured lymphoblastoid cell lines: one line (TSCE5) bears a wild-type p53 gene status, and another line (WTK1) bears a mutated p53 gene status. Under 1 gravity or microgravity conditions, the cells were grown in the cell biology experimental facility (CBEF) of the International Space Station for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…In fact, previous studies have reported regulation of actin polymerization and plasma membrane blebbing by CXCR4-RhoA signaling [159,160]. In [163,164].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have reported regulation of actin polymerization and plasma membrane blebbing by CXCR4-RhoA signaling [159,160]. In [163,164].…”
Section: Discussionmentioning
confidence: 99%
“…73 Each system (RPM and RWV) that generates tissue-like cell assembles under microgravity conditions, initially induces an enhanced rate of apoptosis together with an increase in proapoptotic factors. 10,53,60,[74][75][76] In EC, apoptosis seems to impair the angiogenic response to s-mg produced on the RPM. 77 NF-kB1 plays a central role in bone reduction under microgravity conditions.…”
Section: Known Mechanisms Involved In Spheroid Formationmentioning
confidence: 99%
“…Gene expression patterns in cultured human lymphoblastoid cells during the same spaceflight have already been reported (Takahashi et al, 2010b). In response to space radiation during spaceflight, p53-dependent up-and down-regulated gene expression was found for 111 and 177 genes, respectively (Takahashi et al, 2010b).…”
Section: Msh2mentioning
confidence: 81%
“…In response to space radiation during spaceflight, p53-dependent up-and down-regulated gene expression was found for 111 and 177 genes, respectively (Takahashi et al, 2010b). Only four genes, AF217970, TNFAIP2, cerebellin 3 precursor (CBLN3), and the zinc finger DHHC domain (ZDHHC11) demonstrated p53-dependent down-regulated gene expression during and after spaceflight.…”
Section: Msh2mentioning
confidence: 99%